The relationship between financial liberalization and stock market efficiency: A study of emerging markets / Navaz Naghavi - Navaz, Naghavi (2014)

(untitled)
The process of neoliberal globalization has been associated with successive financial crises during the 1990s. Mexican and Turkish crises of 1994 have culminated with the widespread Asian crisis of 1997; the Russian crisis of 1998, and the possibility of an impending crisis in Brazil during the early months of 1999 have raised serious doubts about the success of uncontrolled movements of capital. Moreover, global financial meltdown in 2008, which can be interpreted as the main challenge of neoliberal globalization, emerged as the most debatable issue of the century. Some economists and policymakers have opined that current financial crisis heralds the failure not only of an economic system, but also of the ideology of free market and neoliberalism. On the other side, in contrast to classical pessimistic view of freedom, modern psychologists assume that freedom has a positive influence on subjective wellbeing. Residents of countries with open economies are experiencing the positive consequences of more economic and financial freedom. In consideration of the aforementioned concerns, it is investigated whether the global financial and economic crisis is a crisis of neoliberalism. Moreover, the diverging results of empirical literature about the liberalization effects is justified based on the pre-requisite economic conditions. Specifically, panel unit root test, panel cointegration, panel Granger causality, General Methods of Moment (GMM) modeling, as well as threshold panel regressions, are the main econometric techniques applied to explore the aforementioned issues. iii Principally, these analyses can be categorized into three major parts. First, this research examines the causal direction between financial liberalization and emerging stock market efficiency in short- and long-term. Second, the effect of financial openness on stock market efficiency has been examined with respect to trade openness and quality of institution as pre-requisite conditions for benefiting from financial liberalization. Once the presence of quality of institutions and trade openness are confirmed as essential and imperative factors, the third analytical section focuses on measuring the critical level of institutions above which an economy can enjoy the beneficial effects of financial liberalization. Similarly, it is posited that, below the threshold level, the country may be in danger of experiencing crisis. Several key findings are worth mentioning here. The empirical evidence on the effects of financial market openness implies the likelihood of a deteriorating impact on stock market efficiency in the short term, as the risk and cost aspect of liberalization initially impede stock market efficiency. However, in the long term, as the stock market participants had time to adjust to the external shocks, they would move to produce more disclosures. Moreover, the study findings lend empirical support to the existence of a significant link between financial openness and stock market efficiency in countries with high institutional quality. It is shown that the success and failure of financial liberalization are assumed to be dependent on country characteristics. This premise implies non-linear relationship (U-shaped) between financial liberalization and stock market efficiency. This U-shaped relationship reveals that, below a certain level of institutions, financial liberalization may lead the market to experience more stock autocorrelation and consequently start moving towards crisis. On the other hand, once the threshold level is reached, financial liberalization has the ability to boost up stock market efficiency.